Particle Distribution, Film Formation and Wear Performance of Brush Plated Ni/WC. Issue 9 (16th June 2018) - Isern, L.; Impey, S.; Clouser, S. J.; Milosevic, D.; Endrino, J. L.
Abstract : Nickel-matrix composite coatings with tungsten carbide particles were produced by brush electroplating using different current densities and materials of the brush. Non-abrasive materials and high current densities produce coatings with high particle content and non-uniform dispersion. Abrasive wear testing showed premature coating failure in areas with high particle concentrations (>21.3 at.% of W). Changes to the solution flow direction were undertaken to decrease 'solution pooling', as it was related to areas with excessive particle content. This, together with the use of abrasive brushes at lower current densities, gives Ni/WC coatings with a low and narrow composition range (from 13.2 ± 4.8 to 2.8 ± 0.8 at.% of W). Such optimized coatings minimized premature coating failure and improved the wear resistance to 1.8–4.4 times that of the original nickel matrix, achieving values similar to hard chrome coatings tested under the same conditions. Unlike other brush plated composite coatings, changes in coating morphology are not heavily influenced by processing parameters, but are sensitive to the presence of WC particles.